Computer-Assisted Piezoelectric Surgery. Issue 3 (May 2015) - Bianchi, Alberto; Badiali, Giovanni; Piersanti, Luigi; Marchetti, Claudio
<x xml:space="preserve">Abstract</x> Purpose: The purpose of the current study was to present the clinical applications of a new technique that we term computer-assisted piezoelectric surgery (CAPS). The method marries piezosurgery and navigation to greatly aid the treatment of various maxillofacial problems. Methods: Preliminary applications in orthognathic surgery, craniofacial procedures, orthodontic surgery, and oncology were analyzed retrospectively. Eighteen patients were treated using the CAPS technique in the interval of 2010 to 2013. Results: The technique emphasizing the features that are not possible without the combination of the 2 systems has been analyzed. The technique is safer than other methods, is minimally invasive, and allows the use of a buried or semiburied approach. Conclusions: According to our preliminary experience, CAPS seems to be a valuable new technique for craniomaxillofacial osteotomies.